Beneficiation of Iraqi Akash at Phosphate Ore Using Organic Acids for the Production of Wet Process Phosphoric Acid - Haweel, C.Kh.; Abdul-Majeed, Basma A.; Eisa, Mohammed Y. (Al-Khwarizmi Engineering Journal, 2013)
In the present work, leaching process studiedusing organic acids (acetic acid and lactic acid) to extract phosphate from the Iraqi Akashat phosphate ore by separation of calcareous materials (mainly calcite). This approach characterized by energy conservation, environmental enhancement by recovery of calcite as calcium sulfate (gypsum), keeping the physical and chemical properties of apatite. Samples were analyzed using X-ray diffraction and FTIR spectrophotometer. From the obtained experimental data it was found that using the two organic acids yields closed purity values of the produced apatite at the optimum conditions, while at different acid concentrations, it was found that the efficiency of acetic acid is higher at the low acid concentration (2 wt%), and that lactic acid gives the higher efficiency at high acid concentration (10 wt%).Concerning the ratio of acid volume to ore weight ratio, it was found that reducing this ratio to 5 ml/gm cause an increase in the purity of apatite at the optimum concentrations of the two acids. In addition, it was found that the reaction ofthe two organic acids with the calcareous material are fast and that the optimum reaction time, in which high purity apatite produced is 10 minutes.